The immune reaction against allogeneic necrotic cells is reduced in Annexin A5 knock out mice whose macrophages display an anti-inflammatory phenotype - Frey, Benjamin; Munoz, Luis Enrique; Pausch, Friederike; Sieber, Renate; Franz, Sandra; Brachvogel, Bent; Poschl, Ernst; Schneider, Holm; Roedel, Franz; Sauer, Rolf; Fietkau, Rainer; Herrmann, Martin; et al. (Journal of Cellular and Molecular Medicine, 2009)
Proteins of the annexin family bind to phospholipids in a Ca2+ dependent manner. The exposure of phosphatidylserine (PS) by apoptotic as well as necrotic cells is one major eat-me-signal for macrophages. Annexin A5 (Anx A5) preferentially binds to PS. The availability of Anx A5 knock out (KO) mice allowed us to investigate for the first time if endogenous Anx A5 modulates the immune response towards allogeneic cells. Furthermore, the effect of Anx A5 gene deletion on the phagocytic process as well as on the inflammatory reaction of macrophages was explored. We found that Anx A5 KO mice have a strongly reduced allogeneic cellular immune reaction against primary as well as secondary necrotic cells. In vivo phagocytosis experiments revealed that macrophages of Anx A5 KO mice displayed an increased uptake of necrotic cells. Additionally, an increased secretion of the anti-inflammatory cytokine IL-10 of isolated macrophages of Anx A5 KO mice after contact with necrotic cells was observed. Furthermore, the promoter activity of the Anx A5 gene was enhanced after stimulation of macrophages. The tumour size of an allogeneic tumour regressed faster when endogenous Anx A5 was present. These data demonstrate that endogenous Anx A5 influences the phagocytosis of necrotic cells, modulates the immune response towards allogeneic cells and acts as an inflammatory protein. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Allogeneic cells; Annexin A5; Immune modulation; Inflammation; Macrophages; Phagocytosis; Primary necrosis; Secondary necrosis